PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KARAKTERISTIK INDIVIDU, LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA DAN KINERJA GURU SMK NEGERI 1 TAMBELANGAN SAMPANG - Imam Soetopo; Amiartuti Kusmaningtyas; Tri Andjarwati (Universitas 17 Agustus 1945 Surabaya, 2018)
The purpose of this study was to analyze the effect of the influence of transformationalleadership style, individual characteristics, work environment on work motivation and teacherperformance. The study was conducted at State Vocational School Tambelangan 1 , SampangRegency, with 40 teachers as respondents. Data collected with survey methode and questionnaireis as instrument. This research is included in associative research. The data obtained is analyzedusing SPSS. The results of the study were obtained, that Transformation Leadership Style has nosignificant effect on Work Motivation, Individual characteristics have no significant effect onWork Motivation, Work Environment has no significant effect on Work Motivation,Transformational Leadership has significant effect on Teacher Performance, IndividualCharacteristics have a significant effect on Teacher Performance, Work Environment has nosignificant effect on Teacher Performance, and Work Motivation has no significant effect onTeacher Performance.Keywords: Transformational Leadership Style, Individual Characteristics, Work Motivation